A new species of Kamaka (Amphipoda: Kamakidae) from Lake Tonle Sap, Cambodia - Morino, Hiroshi (Zootaxa, 2012)
Kamaka tonlensis sp. nov. is described from Lake Tonle Sap, Cambodia. This species is peculiar in having no marginal setae onthe outer ramus of uropod 2 and relatively elongate dactylus of male gnathopod 1. It brings the number of species of Kamaka up to 13.Keywords. Crustacea, Amphipoda, Kamakidae, Kamaka tonlensis, new species, Cambodia, Lake Tonle Sap